Kadar Klorofil Daun Mangrove Di Kawasan Pelabuhan Hurnala Maluku Tengah - Asyik Nur Allifah A.F.; Nur Alim Natsir; Nina Y. Mulyawati; Surati (Biotropic : The Journal of Tropical Biology, 2022)
The aim of this study was to determine the chlorophyll content of mangrove leaves in the Hurnala port area of ​​Central Maluku. This research was conducted on June 24 – August 24, 2021 in the Hurnala port area of ​​Central Maluku. Sampling was carried out of mangrove leaves at three sampling stations at station 1 (boat berth), station 2 (Hurnala port) and station 3 (Estuary of the river). The chlorophyll content test was carried out in the Laboratory of Biochemistry and Organic Chemistry, Faculty of Mathematics and Natural Sciences, Department of Chemistry, Pattimura University, Ambon with UV-Vis spectrophotometer using 652 nm and 665 nm. The results showed that the chlorophyll content of mangrove leaves was at station 2 (17.3362 g/mL), station 3 (8.2885 g/mL) and station 1 (7.0349 g/mL).